PLANNING OF FLOATING FOUNDATION FOR SOFT SOIL IN GLAGAH AGUNG, BANYUWANGI CITY - Dora Melati Nurita Sandi; Erna Suryani; Ayu Wanda Febrian (Universitas Jember, 2019)
Soft soil in construction often creates a problem. Soft soil which has the characteristics of low bearing capacity and high shrinkage properties becomes a problem for construction. One of the efforts to overcome these problems is by planning building foundations that are following soft soil characters. A floating foundation is planned that adopts the concept of lightweight concrete. The lightweight concrete used is an innovative concrete that uses styrofoam as a substitute for coarse aggregate. So that this concrete does not require broken stone or gravel as a concrete filler. Initial planning for floating foundations was carried out in the Purwoharjo area. Soil samples are taken and analyzed their characteristics to get the soil parameters. Then the dimensions of the foundation are planned by using the terzaghi formula for shallow foundations. The decrease or settlement of the soil was analyzed using the help of PLAXIS 2D software. Tanah lunak dalam konstruksi seringkali menjadi sebuah kendala. Tanah lunak yang memiliki karakteristik daya dukung rendah dan sifat kembang susut tinggi menjadi sebuah permasalahan dalam mendirikan bangunan di atasnya. Salah satu upaya untuk mengatasi permasalahan tersebut adalah dengan merencanakan pondasi bangunan yang sesuai dengan karakter tanah lunak. Direncanakan sebuah pondasi apung yang mengadopsi konsep beton ringan. Beton ringan yang digunakan merupakan beton inovasi yang menggunakan styrofoam sebagai pengganti agregat kasarnya. Sehingga beton ini tidak memerlukan batu pecah atau kerikil sebagai bahan pengisi beton. Perencanaan awal untuk pondasi apung, dilakukan di daerah Purwoharjo. Sample tanah diambil dan dianalisis karakteristiknya untuk mendapatkan parameter-parameter tanahnya. Kemudian direncanakan dimensi pondasi dengan menggunakan rumus terzaghi untuk pondasi dangkal. Penurunan atau settlement tanah dianalisis menggunakan bantuan software PLAXIS 2D.